(untitled) (E Conference Zone, 2023)
The article examines the interdependence of ecology and economy, the impact and results of the country’s economic activity on the environment. The benefits of transition to a "green economy" will be highlighted in order to significantly reduce environmental risks arising from the country’s economy and production. In addition, this article analyzes and studies the annual reports of the World Bank on the transition to the "green economy".